Investigating university English as a foreign language instructors’ implementations in teaching integral listening with speaking - Addisu Bogale Shago; Elias Woemego Bushisso; Taye Gebremariam Olamo (PLoS ONE, 2025)
Employing integral instruction of listening and speaking, and understanding their roles is significant for effective language teaching, developing learners’ spoken and written proficiencies, and improving their achievement and motivation. However, there is limited prior research on EFL-integrated listening and speaking in public universities in Ethiopia. Investigating the integral teaching/learning of listening and speaking remains a research problem. Accordingly, the study aims to examine University English EFL instructors’ implementations in teaching integral listening and speaking employing a concurrent mixed-methods design. A total of 252 sample respondents were involved in data collection. Comprehensive and systematic sampling techniques were used to select respondents using a 5-point Likert scale. Through purposive sampling, 12 instructors were identified for qualitative data collection employing semi-structured observations and interviews. Quantitative data analysis employed descriptive and inferential statistics run by SPSS version 20. Qualitative data were thematically analyzed utilizing NVIVO 12 Pro. The findings revealed a remarkable mismatch between EFL instructors’ reported practice and the implementation of integral teaching of listening and speaking. Students’ questionnaire data confirmed the mismatch between the results of the instructors’ practice and implementation. The main themes predicted integral practice included using real-life listening materials, appropriate application of listening phases, and using the language features appropriately. The variance was indicated by the effect size with an eta-squared value of 75%. Qualitative findings supported that EFL teachers frequently relied on non-authentic listening materials. The study implied that EFL program development and curriculum reviews incorporate key factors influencing integral instruction of listening and speaking in the present study. Finally, the study provided recommendations for EFL teachers and the contexts beyond the present settings.